Risk Factors and Incidences for Neonatal Hyperbilirubinemia in Erbil-City: A Cross-Sectional Study - Haydar Saber, Muzhda; Noori Saleh, Goran; Noori Saleh, Karzan; Bakir Muhammad Banna, Hiwa (Al-Nahrain Journal of Science, 2025)
Neonatal hyperbilirubinemia is a common condition in newborns, defined by increased bilirubin levels usually manifested as jaundice. In the present review, the incidence of neonatal hyperbilirubinemia and its risk factors will be discussed in Erbil, Kurdistan Region of Iraq. A cross-sectional study was done on 100 full-term neonates admitted into three hospitals from January to April 2023. The analysis identified maternal factors such as age, mode of delivery, and type of anesthesia in relation to neonatal factors of mode of feeding, gestational age, and blood type. In this regard, the mode of feeding and type of anesthesia used at birth showed a strong association with hyperbilirubinemia but not with maternal age, blood group, and Rh factor. In particular, this will be crucial in avoiding serious consequences, especially for prematurely born infants. Further investigations are recommended with larger sample sizes in order to study other possible risk factors. In conclusion, the study shows that feeding habits and delivery anesthetics strongly influence newborn hyperbilirubinemia. Although maternal age, educational level, and Rh factor were not statistically significant, and the need of early screening and focused therapy to minimize poor outcomes, especially in high-risk neonates such preterm newborns. To identify more risk variables and improve newborn care, bigger studies are necessary.